Constructing a Human World: Denis Williams's Place in British Modernism of the 1950s. Issue 3 (28th June 2021) - Thompson, Allison
Abstract : This essay examines two paintings by Denis Williams, Human World (1950) and Painting in Six Related Rhythms (1954), and their accompanying critical reception, to consider the transformation that takes place from an early interest in social realism and narrative approach in representing the post‐war urban environment and the experience of migration in London, to a radically geometric abstraction that deliberately negates any narrative reference. Wyndham Lewis was a fervent supporter and mentor, but his writings on Williams employed clichéd characterizations of primitivism and colonialism that limited a fuller understanding of the artist's intentions for his work. Wilson Harris's more fully considered essays provide an interesting counterpart. Williams's contribution to British modernism of the 1950s, which was largely eclipsed following his departure for Africa and eventual return to Guyana, should, it is argued, be reconsidered as part of a fuller and more inclusive assessment of that period.